GAMBARAN PERILAKU PROSOSIAL ANAK USIA PRA SEKOLAH DI TK MARIA FATIMA JEMBRANA BALI - Ni Luh Made Asri Dewi (Bali Health Published Journal, 2019)
Background: Prosocial behavior is one type of social-emotional development among preschoolers which can influence development at a later stage. Untreated social-emotional development can lead to aggressive, shy, timid, destructive behaviors, powerful behavior, violent behavior, negativism and selfishness. Objective to describe the prosocial behavior among preschoolers (5-6 years). Methods: This study used a descriptive design with a survey approach. The sampling technique used in this study was probability sampling: total sampling, namely 66 preschoolers (5-6 years old) at Maria Fatima Kindergarten, Jembrana, Bali. The data collection tool used here was a questionnaire in the form of a scale that was developed based on prosocial behavior indicators. Data analysis used univariate analysis in the form of categories. Results: The study results showed the characteristics of respondents namely male children of 48.5%, female children of 51.5%, five years old of 69.7%, six years old of 30.3%. The minimum score of prosocial behavior was 25 (low category) and the maximum score was 39 (moderate category). Conclusion: This study found that most of prosocial behavior of preschoolers (5-6 years old) was in the moderate category (74.2%). Further studies should be conducted regarding the factors that influence prosocial behavior.